Study on the Application of the GTAW Process in Strengthening the Welding Quality of Short Duplex Stainless Pipe - Ming-Che Lin; Chia-Chieh Cheng; Ching-Chien Huang (Metals, 2022)
This study focuses on the results of the welding process when the Taguchi method is added to the design of experimental welding parameters when creating the welding procedure for gas tungsten arc welding (GTAW) by ASME Code for duplex stainless steel (UNS31803). A Vickers hardness tester is employed to collect and convert the tensile strength data for each test piece (weld bead, base material, and heat-affected area). A ferritic rate meter can quickly determine the ferric contents, which affect corrosion resistance and susceptibility to cracking. The test data are entered into the Taguchi technique to analyze the influence of each component on the welding quality. The L9 (34) orthogonal table is used to design the parameters for the experiment. We fixed the same shielding gas and flow rate. Backing gas at root, workpiece clamping angle, heat input, and interlayer temperature are employed as control factors for the four essential variables of the GTAW process. The ideal set of quality analysis and optimization parameters can be found. The welding parameters could be used to improve the welding quality of thin and short duplex stainless steel pipe fittings during argon welding.